Rising Food Inflation in Nigeria: Do Monetary Policy Interventions Matter? - Innocent Chile Nzeh (Universitas Airlangga, 2025)
Objective: The rising cost of food in Nigeria, especially in recent times, has increased the level of hunger and frustration among Nigerians. Consequently, several policies have been put in place to increase food productivity on the one hand and reduce the high level of food inflation on the other. This study examined the response of food inflation to the CBN’s manipulation of monetary policy tools. The novelty introduced in this study is the use of the vector autoregressive (VAR) model in the analysis of the response of food inflation to the manipulation of monetary policy tools in Nigeria. Methods: The study used monthly data that spanned the period from 2007M12-2024M5, while the VAR framework was adopted for analysis. Findings: The study found that food inflation responded positively to shocks in the broad money supply (M2) across all periods, except period one. It was also found that, while food inflation responded negatively to the monetary policy rate (MPR), the Treasury bill rate (TBR), and bank reserves in the majority of periods, its response to the exchange rate was positive in all periods. In another respect, the findings indicate that the monetary authorities responded positively to shocks in food inflation by manipulating the MPR, TBR, and the exchange rate. In particular, the MPR, TBR, and exchange rate responded positively to shocks in food inflation during the study period. Originality/Value: This study contributes to extant literature through methodology. It applies the vector autoregressive (VAR) model in the analysis to take care of the possible feedback arising from the implementation of monetary policy. This approach departs from previous studies in Nigeria which adopted frameworks such as the autoregressive distributed lag (ARDL) model and the non-linear ARDL. Practical/Policy implication: Address food inflation using monetary policy tools and complementing them with fiscal policies. In addition, the exchange rate policy should be adjusted to favour food imports in the short run, while the long-run target should be to increase domestic food production through various measures.